Evaluasi Pengalaman Pengguna pada Transisi Learning Management System di Pendidikan Tinggi - Baskara, Elan; Damayanti, Anindya; Buwana, Penta Eva Tri (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
Sekolah Tinggi Multi Media (STMM) Yogyakarta recently transitioned from an internally managed Moodle-based Learning Management System (LMS) to a vendor-provided cloud platform. Despite lecturers serving as primary LMS operators for material upload, assignment management, and attendance recording, no systematic user experience (UX) evaluation of this transition has been conducted. This study compares lecturer UX across both systems using the User Experience Questionnaire (UEQ), a validated instrument measuring Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. A within-subject comparative design was applied to 20 STMM lecturers selected from 72 total lecturers, specifically those who regularly used all three mandated LMS functions in both systems. Two UEQ sets were administered: one retrospective (old LMS) and one current (new LMS). Wilcoxon Signed-Rank test and paired t-test were applied with Bonferroni correction (alpha = 0.0083). Stimulation (d = 0.893; p = 0.001) and Novelty (d = 0.882; p = 0.001) showed significant large improvements, both surviving correction. Pragmatic scales showed no significant differences. Key limitations include the retrospective design and poor reliability on several old LMS subscales. Findings show LMS migration primarily enhances hedonic quality, offering a replicable evaluation framework for institutions planning similar transitions.